What women want: General population perspectives and access to preconception expanded carrier screening. (1st July 2021) - Rabkina, Liya; Swanson, Amy; Aufox, Sharon; Propst, Lauren; Fiddler, Morris; Wagner, Andrew; Arjunan, Aishwarya
Abstract: Objective: Expanded carrier screening (ECS) assesses the risk of individuals and couples of having a child affected with a set of genetic conditions. Carriers have options available to optimize pregnancy outcomes based on personal values and preferences. The greatest range of options is available prior to pregnancy, therefore professional societies recommend this screening be performed preconception. This study aimed to assess awareness of, and interest in, ECS in women preconception. Additionally, it aimed to evaluate preferences for timing and location of education and availability of ECS. Methods: A total of 260 nulliparous women from the general population were surveyed through Qualtrics, a national market research survey platform. Data were delineated using descriptive statistics. Results: Of this cohort, 43.5% reported being aware of ECS prior to the survey and 77.8% indicated interest. Those previously aware were first informed by family, friends, or independent online research. Interest was primarily driven by a desire for reassurance and to make informed decisions about future pregnancies. Interested respondents indicated a willingness to request testing from providers. Participants showed a preference for education and access from a healthcare provider in person. Conclusion: These findings provide insight regarding when and where to best educate and reach women prior to pregnancy about ECS to maximize pregnancy outcomes. Key Points: Why was the study conducted? What is already known? Ideally, carrier screening is performed in the preconception period, however, the majority of carrier screening tests actually occur in the prenatal period. Prior studies have focused on the provider perspective. This study aimed to assess the awareness of carrier screening in nulliparous women and their motivation for pursing such screening What does this study add to what is already known? This study showed that the majority of women are interested in expanded carrier screening so that they can make informed decisions about future pregnancies. Participants preferred this information to be presented to them by their healthcare providers even though many learned about it from family, friends or independent research. This study provides insight on when and where to best educate and reach women in the preconception period about expanded carrier screening